2009
DOI: 10.1177/0888406409346144
|View full text |Cite
|
Sign up to set email alerts
|

Examining Perceptions of Systematic Integration of Instructional Technology in a Teacher Education Program

Abstract: In this article, the authors describe a systematic effort by a department of special education to integrate technology into teaching through a one-to-one laptop initiative and to examine preservice teachers' perceptions concerning their experiences with the initiative. The authors investigate beliefs about preservice teachers' proficiency in using technology for teaching, their attitudes toward the use of technology for teaching, and their perceptions of the integration of instructional technology practices by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 6 publications
1
13
0
5
Order By: Relevance
“…In their study, teachers found laptop with multimedia capability allowed them to make more use of visual materials and promoted students' understanding and interest. Our results also parallel the findings from Allsopp's [16] survey that examined perceptions of integrating technology in a teacher education program. The result of the survey suggested that pre-service teachers' self-perception of their ability to use technology for teaching increased.…”
Section: The Way 1:1 Computing Changes Preservice Teachers' View On Tsupporting
confidence: 82%
“…In their study, teachers found laptop with multimedia capability allowed them to make more use of visual materials and promoted students' understanding and interest. Our results also parallel the findings from Allsopp's [16] survey that examined perceptions of integrating technology in a teacher education program. The result of the survey suggested that pre-service teachers' self-perception of their ability to use technology for teaching increased.…”
Section: The Way 1:1 Computing Changes Preservice Teachers' View On Tsupporting
confidence: 82%
“…Evidently, teachers' self‐efficacy beliefs regarding technology integration have been known to predict their intentions to use technology (Anderson & Maninger, ; Oliver & Shapiro, ; Wang et al, ). Extensive empirical research has documented the critical links between preservice teachers' technology self‐efficacy and their intentions to integrate technology into their future classrooms (Anderson, Groulx, & Maninger, ; Banas & York, ), attitudes toward technology integration (Allsopp, McHatton, & Cranston‐Gingras, ; Rehmat & Bailey, ), and technology acceptance and satisfaction (Holden & Rada, ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, colleges of education have intensified their efforts to integrate technology directly into methods courses, giving students the opportunity to carry out what they have learned (Allsopp, McHatton, & Cranston-Gingras, 2009). Due to this effort, teacher candidates may show signs of gains in technology comfort levels, but this does not necessarily translate into effective technology use within lesson plans (Mayo & Kais, 2005).…”
Section: Teacher Technology Preparation In Pre-service Trainingmentioning
confidence: 99%